Impact of Control on Performance Appraisal (Case Study Ministry of Education. South Dar Fur State, Republic of Sudan) - Hissin, Magbola AbdoAljabar; Ahmed, Alamin Mohammed Adam; Mohamed, Musa Salih Omer; Gojah, Ali Yahya (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aimed to study the impact of control on performance appraisal in the Ministry of Education, South Dar fur, Sudan, also aimed to study the following objectives:1. The impact of control on employee's performance appraisal.2. To measure the dimensions of control (Reports, Observation, and Complains) on performance appraisal.3. Performance appraisal can be adopted as one of the most important issues that affecting services and employee's performance. The research looking forward to find an answer to the research problems such as:1. Is there any relationship between administrative reports and performance appraisal in the Ministry of Education?2. Is there any relationship between observation and performance appraisal in the Ministry of Education?3. Is there any relationship between employees complains and performance appraisal in the Ministry of Education?To have an answer for above mentioned problems we adopted analytical methods for data analysis and we reached the following findings:1.There any relationship between administrative reports and performance appraisal in the Ministry of Education?2. There any relationship between administrative reports and performance appraisal in the Ministry of Education?3. There any relationship between administrative reports and performance appraisal in the Ministry of Education?For good control there should be a well-known criteria and stander according to which employee's works can be check efficiently and effectively. The need for good control comes to the work because of the big size of organizations and the number of employees.
Keywords: Control; Administrative reports; observation; complains and performance appraisal